Jika f(x)= 2x dan f(g(x)) = -x/2+1, fungsi g(-x) =…

Posted on

Jika f(x)= 2x dan f(g(x)) = -x/2+1, fungsi g(-x) =...

Jika f(x)= 2x dan f(g(x)) = -x/2+1, fungsi g(-x) =…

Jawaban:

Jawabannya C. g(-x) = 0,25 ( x + 2)

Penjelasan dengan langkah-langkah:

  • Diketahui : f(x) = 2x
  • f(g(x)) = x/2 + 1
  • Ditanya : g(x) = .....?
  • Jawab :
  • f(g(x)) = x/2 + 1
  • 2(g(x)) = x/2 + 1
  • g(x) = ( x/2 + 1) /2
  • g(x) = x/4 + 1/2
  • g(x) = x/4 + 2/4
  • g(x) = ¼(x+2)

Maka

  • g(x) = ¼((x) + 2)
  • g(x) = ¼(x+2)
  • g(x) = ¼(x+2)
  • Karena ¼ = 0,25
  • Maka :
  • g(x) = 0,25 ( x + 2)
  • JAWABANNYA C